2015
DOI: 10.1373/clinchem.2014.229328
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Prenatal Testing for Wilson Disease by Use of Circulating Single-Molecule Amplification and Resequencing Technology (cSMART)

Abstract: BACKGROUND:Noninvasive prenatal testing (NIPT) for monogenic diseases by use of PCR-based strategies requires precise quantification of mutant fetal alleles circulating in the maternal plasma. The study describes the development and validation of a novel assay termed circulating single-molecule amplification and resequencing technology (cSMART) for counting single allelic molecules in plasma. Here we demonstrate the suitability of cSMART for NIPT, with Wilson Disease (WD) as proof of concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 40 publications
0
71
0
2
Order By: Relevance
“…Son zamanlarda, Wilson hastalığı riski taşıyan gebeliklerde fetal genotiplerin tanısında kullanılabilecek noninvaziv bir prenatal test geliştirilmiştir (25). Bizim olgularımızda da her trimesterde serum seruloplazmin, karaciğer ve böbrek fonksiyon testleri, pıhtılaşma profili, tam kan sayımı ve tam idrar tetkiki anne için tekrarlanmıştır.…”
Section: Discussionunclassified
“…Son zamanlarda, Wilson hastalığı riski taşıyan gebeliklerde fetal genotiplerin tanısında kullanılabilecek noninvaziv bir prenatal test geliştirilmiştir (25). Bizim olgularımızda da her trimesterde serum seruloplazmin, karaciğer ve böbrek fonksiyon testleri, pıhtılaşma profili, tam kan sayımı ve tam idrar tetkiki anne için tekrarlanmıştır.…”
Section: Discussionunclassified
“…In addition to the UMI approach, other error-suppression strategies are also being developed and can be potentially applied to cfDNA to solve the technical shortcomings of conventional PCR on cfDNA. For example, a method dubbed 'circle sequencing' uses CircLigase to circularize denatured single-stranded (ss) DNA fragments, followed by inverse PCR or rolling circle amplification (RCA) ( Figure 2) [38,40]. Unlike conventional PCR, which requires two PCR landing sites flanking the targeted region, inverse PCR primers can be designed adjacent to each other; therefore, it is particularly advantageous in recovering gene fusions with unknown fusion partners ( Figure 2A).…”
Section: Somatic Mutationsmentioning
confidence: 99%
“…Currently, to perform prenatal diagnosis on these monogenic disorders, invasive procedures such as chorionic villus sampling or amniocentesis are required. A proof-of-principle study has already shown that monogenic disorders can also be accurately diagnosed prenatally via liquid biopsy [40]. The clinical implementation of NIPD for monogenic disorders will be the next breakthrough of molecular diagnosis in the prenatal health field.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Haplotype based targeted sequencing of maternal plasma has been shown to be accurate for the diagnosis of HHL (22) and SMA (23). Further, an alternative NIPT method called circulating single molecule amplification and re-sequencing technology (cSMART) has also been demonstrated to accurately genotype the fetus in pregnancies at risk for Wilson Disease (24). In principle, even if there is no knowledge of the causative parental mutations, it is possible to develop these two technologies further for the diagnosis of a broader range of monogenic diseases.…”
Section: Next Generation Sequencing Technologies For Prevention Of Gementioning
confidence: 99%